Variation of activity demands in small-sided soccer games - Dellal, A.; Drust, B.; Lago-Penas, C. (International Journal of Sports Medicine, 2012)
The aim of the present study was to examine the physical and technical activity during different periods within small-sided soccer games (SSGs). 20 elite players completed 3 different SSGs (2-a-side, 3-a-side and 4-a-side games) in which the number of ball touches per individual possession was fixed at a maximum of 2. The duration and the pitch size of each SSG were strictly controlled (2 min, 3 min, 4 min, respectively; 1:75 m2) with each period repeated 4 times (P1, P2, P3, P4). The physical and technical activities, heart rate responses, blood lactate concentration and rating of perceived exertion (RPE) were analysed. The results showed a decrease of high and very high-intensity activities (from - 26.2% to - 37.7%, P<0.001), an increase of blood lactate concentration (from + 28.0% to + 76.9%), RPE (from + 29.0% to + 32.8%), and heart rate responses (~ 6.6%), and a significant alteration of technical activities from P1 to P4 in each SSG. The greatest differences from P1 and P4 were observed for the 2-a-side game when compared to the 3-a-side and 4-a-side games (P<0.05) for each variable analysed . In conclusion, the variation of the player's activity throughout the periods indicates that the duration and number of exercise periods used within SSGs is an important variable in determining the training stimulus in soccer-specific training.